Does Internal Corporate Governance Complement or Substitute for External Auditing? Evidence from China's Anti‐corruption Campaign. (9th March 2021) - Jin, Qinglu; Jin, Yuchao; Tian, Gary Gang; Xuan, Yang
Abstract : Two competing hypotheses have been developed for the relationship between internal corporate governance and external auditing. One proposes a complementary relationship, while the other suggests it is substitutable. This study takes advantage of China's recent anti‐corruption campaign as a quasi‐natural experiment to explore this relationship. Using a difference‐in‐differences approach, we find that, after the campaign, internal corporate governance improved more in SOEs (state‐owned enterprises) than in non‐SOEs. SOEs were less likely to choose Big 10 auditors after the campaign, while audit firms assigned less experienced auditors to their SOE client firms and charged lower audit fees. These effects were more pronounced in SOEs that exhibited greater improvement in corporate governance. Overall, we find the anti‐corruption campaign improved corporate governance in SOEs but, at the same time, reduced external audit quality, which supports the substitution view. We argue that this result might be driven by the fact that SOEs have limited demand for high‐quality accounting information because the Chinese government maintains strong control over the capital markets.